"Memory - Object - Talent: Art and Design for Social and Cultural Inclusion of Immigrants and Refugees". - Gorgel Pinto, António (2022)
: What kind of art and design practice can be developed to boost the social and cultural inclusion of newly arrived immigrants and refugees to their new places of residence? Is there something the host society can do to involve artists, designers, stakeholders, and citizens to support these vulnerable new fellow citizens, to help them feel more confident with their new lives and promote their emancipation? With this and other questions in mind, we decided to develop a hybrid art and design participatory project with immigrant and refugee communities, which took place in the summer of 2019, in Cedar Rapids, Iowa (US). The political situation of the US, which was at the moment somehow hostile to new immigrants, was the perfect context for our project to make a strong statement. The article starts by contextualizing the project in sociological terms, as well as arguing about this hybrid practice field of participatory art and design, specifically through some paradigmatic case studies. We also focus on other topics that are central to our practice, such as the domain of participation and creative thinking, as well as the importance of strategically considering each part of the project as a specific mechanism. In a more conceptual approach, we also focus on the migrants’ overwhelming situation, inspired by Paulo Freire´s “Pedagogy of the Oppressed,” where he advocates the development of a “praxis” to liberate both the oppressed and the oppressors and promote a righteous society. Following is a description of the methodology used for the interaction with the participants, namely the creation of a specific game, which is a form of self-representation and enhancement of the engaged immigrant and refugee communities. The core of the article is concerned with the project’s playful nature, which is explained according to the concept of game by Hans-Georg Gadamer. The article ends with some extra data collected through interviews, as well as a reflection concerning the experimented practice.